Propuesta De Un Modelo Alternativo De Funcionamiento Del Sistema Turístico - Manuel Antonio Abarca Zaquinaula (European Scientific Journal, ESJ, 2017)
The present study shows an alternative proposal of operation of the tourist system from the perspective of mechanics and their coordinated, harmonious, and routine interrelation between its parts. This study was carried out based on the tourism systems proposed by Roberto Boullón, Neil Leiper, and the World Tourism Organization. The problems that affected the development of tourism in a society was analyzed. It established a systemicmechanical model of four parts rector of the tourist system, real and potential demand, geographical space, and offers tourist system which are interrelated to each other. All have the same importance, different objectives, and the same purpose to satisfy fully the needs for transportation, lodging, food and recreation of the actual and potential tourist demand. This is achieved through the coordinated and effective functioning of the servers and/or entrepreneurs of the geographic space and the vehicle that the tourist offers. Subsequently, it would help to improve and streamline their tourism services and products by adapting them to their needs and trends. This is with the aim of returning them to their place of residence. The present article emphasizes the importance of observing the tourist system as the basic unit in the development of the tourist industry. It states that the lack of understanding of its operation is what has not allowed this industry to develop fully around the world.